Social computing and social media : 8th International Conference, SCSM 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings /: 8th International Conference, SCSM 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings. (2016) - Unknown
No abstract available